Multi-dimensional nano-composite wave-absorbing material as well as preparation method and application thereof

MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing material prepared by double droplet coprecipitation method and hydrothermal method solves the problem of complex and high cost in the preparation process of existing absorbing materials, and realizes efficient electromagnetic wave absorption and The effect of broad spectrum absorption.

CN119430319AActive Publication Date: 2025-02-14WUHAN UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411436543.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

While improving the absorption capacity of electromagnetic waves, the existing wave absorbing materials have a complex and high cost, which limits their wide application in the field of electromagnetic wave shielding.

Method used

The MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing material was prepared by double droplet co-precipitation method and hydrothermal method. By adding low-cost carbon nanotube composite conductive agent and Fe3O4 nanoparticles, the dielectric loss of the material is regulated and Magnetic loss capability.

Benefits of technology

It realizes the efficient electromagnetic wave absorption performance of the wave absorbing material while reducing the cost of raw materials, covers the broad spectrum absorption of Ku, X and C bands, and significantly reduces the amount of MXene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430319A_ABST
    Figure CN119430319A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of wave-absorbing materials, and particularly relates to a multi-dimensional nano-composite wave-absorbing material and a preparation method and application thereof.The preparation method comprises the steps that nickel salt hydrate, cobalt salt hydrate and copper salt hydrate are mixed according to the design proportion and dissolved in water to form a solution A; preparing an alkaline solution B; then adding an MXene dispersion liquid into a container, dropwise adding the liquid A and the liquid B, and keeping the mixed liquid in an alkaline environment; and then adding a carbon nanotube composite conductive agent and Fe3O4 nanoparticles, carrying out heating treatment after normal temperature reaction, and finally carrying out centrifugal separation and washing on the product. The invention innovatively develops the MXene-NiCoCu-Fe-CNT type nano composite hydrotalcite wave-absorbing material which is prepared by a simple double-drop coprecipitation method and a hydrothermal method and has good wave-absorbing performance, and the raw material cost is greatly reduced on the premise of simplifying the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wave-absorbing materials, and in particular relates to a multi-dimensional nano-composite wave-absorbing material and a preparation method and application thereof. Background Art

[0002] With the booming development of the electronic equipment industry and the gradual popularization of 5G networks, electromagnetic waves (EMW) have become commonplace in people's daily lives. At present, the almost ubiquitous electromagnetic waves have brought convenience to people, but also brought electromagnetic pollution that cannot be ignored. It affects the operation of electronic equipment and has various negative impacts on people's health. Against this background, absorbing materials came into being. Absorbing materials have a wide range of applications in civil and military fields, especially in stealth coatings, satellite radars, etc. In order to obtain efficient electromagnetic wave absorbing materials with strong absorption ability, wide absorption bandwidth and as thin a matching thickness as possible, the design of their structure and composition is indispensable.

[0003] Hydrotalcite is a two-dimensional anionic material composed of positively charged layers and interlayer anions. Benefiting from the tunable interlayer space and anions with the positively charged host layer and two-dimensional structure, hydrotalcite has been widely used in many fields such as catalysis, energy storage and adsorption. Despite the versatility and potential of hydrotalcite, there are few reports on its use as EMW absorber. At the same time, traditional single metal oxides such as Fe2O3, Fe3O4, Co3O4, TiO2 and NiO cannot meet the requirements of efficient EMW absorbers due to their own limitations. They are often limited by low conductivity, poor impedance matching and high density. Therefore, many studies have focused on combining metal oxides with other dielectric materials (carbon materials and polymers) through hydrothermal, in situ growth and sol-gel methods to obtain efficient hybrid materials. At present, many carbon materials such as graphene, carbon nanotubes, and MXene have been used to adjust the relative complex dielectric constant and permeability of composites, but their complicated preparation methods and high prices hinder their further application in the field of microwave absorption.

[0004] Traditional hydrotalcite-based absorbing materials often require the addition of large amounts of materials with good conductive properties, such as MXene, graphene, and silicon carbide nanowires, to increase the dielectric loss capacity of the absorbing materials. The complex preparation methods and high prices of these materials hinder their further large-scale application in the field of absorbing materials. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention innovatively develops a MXene-NiCoCu-Fe-CNT type nanocomposite hydrotalcite absorbing material with good absorbing performance prepared by a simple double-drop co-precipitation method and hydrothermal method, and greatly reduces the raw material cost while simplifying the preparation process.

[0006] To achieve the above object, the present invention is implemented by the following technical solutions:

[0007] The invention provides a preparation method of a multidimensional nano composite wave absorbing material, which comprises: mixing nickel salt hydrate, cobalt salt hydrate and copper salt hydrate according to a designed ratio and dissolving them in water to form liquid A; preparing alkaline liquid B; then adding MXene dispersion into a container, adding liquid A and liquid B dropwise, so that the mixed liquid maintains an alkaline environment; then adding carbon nanotube composite conductive agent and Fe3O4 nanoparticles, reacting at room temperature and then heating, and finally centrifuging and washing the product.

[0008] In the above scheme, the double drop coprecipitation method is a kind of low saturation coprecipitation method, that is, according to a certain ratio, the metal salt solution is prepared into a mixed salt solution (SolS) of a certain concentration, NaOH and Na2CO3 are prepared into a mixed alkali solution (SolB) according to a certain ratio, SolS and SolB are simultaneously dripped into a large beaker at a certain dripping speed, the pH of the reaction system is maintained at a constant value, and the reaction is stirred vigorously. After the titration is completed, stirring and aging are continued, and finally the product is obtained by filtering, washing, and drying. The hydrothermal synthesis method is to first slowly drop SolS and SolB together and quickly mix, and then immediately transfer the obtained slurry to a certain temperature for aging for a long time, and finally filter, wash, dry, and grind to obtain the product. This method is characterized in that the nucleation and crystallization processes of hydrotalcite are isolated, and the crystallization process is promoted by increasing the aging temperature and pressure. Since no other impurities are introduced in the hydrothermal synthesis method, the prepared material has excellent characteristics such as fine powder (nanoscale), high purity, good dispersibility, uniform particles, complete grain development, and controllable shape. In addition, the hydrothermal method can avoid shortcomings such as stress-induced defects and phase interactions. More importantly, the hydrothermal method can control the morphology, size, viscosity distribution, etc. of the product by adjusting the reaction conditions.

[0009] As a further optimization scheme of the present invention, the molar ratio of the nickel salt hydrate, the cobalt salt hydrate and the copper salt hydrate is (4.5-5.5):(1.5-2.5):1.

[0010] As a further optimization scheme of the present invention, the nickel salt hydrate is selected from NiCl2·6H2O, Ni(NO3)2·6H2O or NiSO4·6H2O, the cobalt salt hydrate is selected from CoCl2·6H2O, Co(NO3)2·6H2O or CoSO4·6H2O, and the copper salt hydrate is selected from CuCl2·2H2O, Cu(NO3)2·3H2O or CuSO4·5H2O. Among them, chloride has lower cost and better safety.

[0011] As a further optimization scheme of the present invention, the alkaline solution B is a mixture of NaOH solution and Na2CO3 solution. The use of a mixed solution of NaOH and Na2CO3 can more conveniently adjust the pH and control the stable progress of the reaction.

[0012] As a further optimization scheme of the present invention, the pH value of the mixed solution is maintained at 9.5-10.5. Maintaining the pH value at about 10 can make it easier for metal salt ions to react with hydroxide to form a hydrotalcite structure.

[0013] As a further optimization scheme of the present invention, the mass ratio of the MXene, carbon nanotube composite conductive agent and Fe3O4 nanoparticles is (3.75-10):(100-200):(231-462). The added carbon nanotube composite conductive agent and ferrosoferric oxide greatly reduce the amount of MXene used and reduce the cost.

[0014] As a further optimization scheme of the present invention, the room temperature reaction time is 0.5-1.5 hours, and the heating treatment is carried out in a water bath at 70° C. for 3.5-4.5 hours.

[0015] The present invention also provides a multi-dimensional nano-composite wave-absorbing material, and the multi-dimensional nano-composite wave-absorbing material is prepared by the preparation method.

[0016] The present invention also provides an application of the multi-dimensional nano-composite absorbing material, wherein the multi-dimensional nano-composite absorbing material is used for stealth coatings, satellite radars or electromagnetic shielding of electronic equipment.

[0017] As a further optimization solution of the present invention, the thickness of the multi-dimensional nano-composite absorbing material is 2-6 mm.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention incorporates carbon nanotubes into the system of hydrotalcite-type absorbing materials as a tool for regulating the dielectric loss and conductivity of the material. Furthermore, among various types of carbon nanotubes of different specifications, the present invention innovatively selects a carbon nanotube composite conductive agent with a lower cost, whose price-to-weight ratio is only one percent of that of ordinary carbon nanotubes, while maintaining good dielectric loss capacity. A reflection loss of -47dB was achieved at 6.2GHz, and an effective absorption bandwidth of 4.72GHz was achieved at a thickness of 2.4mm. At the same time, by regulating the different thicknesses of the material (2-6mm), broad-spectrum absorption covering the Ku band (12-18GHz), X band (8-12GHz) and C (4-8GHz) bands can be successfully achieved. This means that the MXene-NiCoCu-Fe-CNT type nanocomposite hydrotalcite absorbing material synthesized based on this method has great development and large-scale production potential in the field of absorbing waves.

[0020] In summary, based on the traditional MXene-type hydrotalcite absorbing material, the present invention introduces a low-cost carbon nanotube composite conductive agent to replace the expensive MXene to regulate the dielectric loss capacity of the material, which greatly reduces the amount of MXene used. At the same time, Fe3O4 nanoparticles are added to regulate the magnetic loss capacity of the material, thereby maintaining good absorbing performance while greatly reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a transmission electron microscope (TEM) image of the MXene-NiCoCu-Fe-CNT type nanocomposite hydrotalcite absorbing material prepared in Example 1 of the present invention.

[0022] Figure 2 Transmission electron microscopy (TEM) image of the Fe3O4 nanoparticles selected for the present invention.

[0023] Figure 3 3D graph of the reflection loss (RL) of MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbers with different thicknesses in the range of 1-18 GHz.

[0024] Figure 4 This is a two-dimensional graph of the reflection loss (RL) of the MXene-NiCoCu-Fe-CNT type nanocomposite hydrotalcite absorber with a thickness of 2.4 mm as a function of frequency.

[0025] Figure 5 This is a two-dimensional graph showing the reflection loss (RL) of MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorber materials at different thicknesses as a function of frequency.

[0026] Figure 6 This is a two-dimensional graph of the composite dielectric constant of MXene-NiCoCu-Fe-CNT type nanocomposite hydrotalcite absorbing material varying with frequency in the range of 1-18 GHz.

[0027] Figure 7 This is a two-dimensional graph of the composite magnetic permeability of MXene-NiCoCu-Fe-CNT type nanocomposite hydrotalcite absorbing material varying with frequency in the range of 1-18 GHz.

[0028] Figure 8 This is a two-dimensional graph of the variation of the tangent angle of dielectric loss and magnetic loss of MXene-NiCoCu-Fe-CNT type nanocomposite hydrotalcite absorber with frequency in the range of 1-18 GHz. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.

[0030] The carbon nanotube composite conductive agent used in the embodiment of the present invention is directly purchased from Aladdin Company, which is a carbon nanotube composite conductive agent for lithium-ion batteries. The price is lower than that of MXene and ordinary carbon nanotubes, which is 164 yuan / 25g. MXene dispersion liquid adopts titanium carbide (Ti3C2T x )MXene few-layer dispersion.

[0031] Embodiment 1:

[0032] Take n(NiCl2·6H2O):n(CoCl2·6H2O):n(CuCl2·2H2O)=5:2:1, 713.07mg, 285.52mg, 102.3mg respectively, dissolve in 15ml water as liquid A. V(NaOH):V(Na2CO3)=3.2:1, the molar concentration is 0.5mol / L, mix and use as liquid B. Add 1ml MXene dispersion (concentration is 5mg / ml) to a 100ml round-bottom flask, add liquid A and liquid B dropwise, keep the pH of the mixed solution at 10, until liquid A is added, add 100mg carbon nanotube composite conductive agent and 1mmolFe3O4 nanoparticles. After reacting at room temperature for 1h, transfer to a water bath at 70℃ and continue to react for 4h, centrifuge the product, centrifuge at 10000rpm for 10min, wash 3 times with anhydrous ethanol, and wash 3 times with ultrapure water.

[0033] Example 2

[0034] Take n(NiCl2·6H2O):n(CoCl2·6H2O):n(CuCl2·2H2O)=5:2:1, 713.07mg, 285.52mg, 102.3mg respectively, dissolve in 15ml water as liquid A. V(NaOH):V(Na2CO3)=3.2:1, the molar concentration is 0.5mol / L, mix and use as liquid B. Add 2ml MXene dispersion (concentration is 5mg / ml) to a 100ml round-bottom flask, add liquid A and liquid B dropwise, keep the pH of the mixed solution at 10, until liquid A is added, add 150mg carbon nanotube composite conductive agent and 1mmolFe3O4 nanoparticles. After reacting at room temperature for 1h, transfer to a water bath at 70℃ and continue to react for 4h, centrifuge the product, centrifuge at 9000rpm for 10min, wash once with anhydrous ethanol, and wash twice with ultrapure water.

[0035] Example 3

[0036] Take n(NiCl2·6H2O):n(CoCl2·6H2O):n(CuCl2·2H2O)=4.5:1.5:1, 641.76mg, 214.14mg, 102.3mg respectively, dissolve in 15ml water as liquid A. V(NaOH):V(Na2CO3)=3.2:1, the molar concentration is 0.5mol / L, mix and use as liquid B. Add 1ml MXene dispersion (concentration is 5mg / ml) to a 100ml round-bottom flask, add liquid A and liquid B dropwise, keep the pH of the mixture at 10.5, until liquid A is added, add 200mg carbon nanotube composite conductive agent and 1.5mmol Fe3O4 nanoparticles. After reacting at room temperature for 0.5 h, the mixture was transferred to a water bath at 70°C and continued to react for 3.5 h. The product was centrifuged at 8000 rpm for 10 min, washed twice with anhydrous ethanol and once with ultrapure water.

[0037] Example 4

[0038] Take n(NiCl2·6H2O):n(CoCl2·6H2O):n(CuCl2·2H2O)=5.5:2.5:1, 784.38mg, 356.9mg, 102.3mg respectively, dissolve in 15ml water as liquid A. V(NaOH):V(Na2CO3)=3.2:1, the molar concentration is 0.6mol / L, mix and use as liquid B. Add 0.75ml MXene dispersion (concentration is 5mg / ml) to a 100ml round-bottom flask, add liquid A and liquid B dropwise, keep the pH of the mixture at 9.5, until liquid A is added, add 100mg carbon nanotube composite conductive agent and 2mmol Fe3O4 nanoparticles. After reacting at room temperature for 1.5 hours, the mixture was transferred to a water bath at 70°C and continued to react for 4.5 hours. The product was centrifuged at 9000 rpm for 10 minutes and washed twice with anhydrous ethanol and three times with ultrapure water.

[0039] The present invention takes the product prepared in Example 1 as an example to illustrate its synthesis results and performance characterization:

[0040] Figure 1The transmission electron microscope (TEM) image of the MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing material prepared in Example 1 is shown. It can be seen from the figure that the NiCoCu hydrotalcite in the upper left corner presents a characteristic two-dimensional layer structure with many wrinkles, the middle part is Fe3O4 nanoparticles with irregular morphology combined with each other, and the lower right corner is an extended bifurcated carbon nanotube. These structures combined with each other can produce a large surface area and additional void space, and maintain good magnetic loss and dielectric loss, which is beneficial to the electromagnetic wave absorption of the material as a whole.

[0041] Figure 2 The transmission electron microscope (TEM) image of the Fe3O4 nanoparticles used in the material preparation is shown. Figure 1 The structural composition of the middle part of the sample has the same morphological characteristics and size structure, indicating that the structural composition of the middle part of the sample is Fe3O4 nanoparticles. The irregularly morphological Fe3O4 nanoparticles combined with each other provide the material with an irregular surface and good magnetic properties, enhancing the material's magnetic loss capacity and wave absorption performance, and the overall wave absorption efficiency of the material can be easily adjusted by controlling the dosage.

[0042] Figure 3 A 3D plot showing the reflection loss (RL) of MXene-NiCoCu-Fe-CNT type nanocomposite hydrotalcite absorbers with different thicknesses in the range of 1-18 GHz. Figure 4 It shows that the maximum effective absorption bandwidth reached at 2.4mm is 4.72GHz, ranging from 12.97GHz to 17.69GHz. As can be seen from the figure, the minimum reflection loss of NiCoCu absorber is -47.22dB, corresponding to a frequency of 6.29GHz and a thickness of 5.2mm. The maximum effective absorption bandwidth (EAB) is 4.72GHz with a thickness of 2.4mm, which almost covers the entire Ku band. At the same time, Figure 5 The effective absorption frequency range of the material at different thicknesses is shown. As can be seen from the figure, by adjusting the different thicknesses of the material (2-6mm), broad-spectrum absorption covering the Ku band (12-18GHz), X band (8-12GHz) and C band (4-8GHz) can be successfully achieved. In summary, the synthesized MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing material has excellent absorbing performance in the entire frequency range.

[0043] Figure 6The composite dielectric constant of MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing materials in the range of 1-18 GHz, including the real part and the imaginary part, is shown. As can be seen from the figure, with the increase of frequency, the real part (e') and the imaginary part (e") of the composite dielectric constant are partially reduced. In the range of 1-8 GHz, the real part decreases from 8.9 to about 6.1, and the imaginary part decreases from 3.5 to about 2.1; in the range of 5-18 GHz, the real part is maintained between 5-6, and the imaginary part is maintained between 1-2. In summary, the synthesized MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing materials have good dielectric storage and loss capabilities in the entire frequency range.

[0044] Figure 7 The composite magnetic permeability of the MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorber in the range of 1-18 GHz, including the real part and the imaginary part, is shown in the figure. As can be seen from the figure, with the increase of frequency, the real part (u') of the composite magnetic permeability is maintained between 0.8 and 1.0; the imaginary part (u") decreases from 0.78 to about 0.2 in the range of 1-5 GHz, and is maintained between -0.1 and 0.2 in the range of 5-18 GHz. In summary, it is shown that the synthesized MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorber has a certain magnetic storage and loss capacity in the entire frequency range.

[0045] Figure 8 The tangent angles of the dielectric loss and magnetic loss of the MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing material in the range of 1-18 GHz are shown to indicate the material's loss capacity for electromagnetic waves. As can be seen from the figure, within 1-3 GHz, the material's magnetic loss capacity is greater than the dielectric loss capacity, with a peak magnetic loss of 0.78 at 1.2 GHz, and then decreases to 0.4; within 3-18 GHz, the magnetic loss capacity is less than the dielectric loss capacity, and decreases with increasing frequency, and finally fluctuates around 0.1. The dielectric loss capacity is more stable, mainly maintained at around 0.3. In summary, the synthesized MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing material has a certain magnetic storage and loss capacity in the entire frequency range, and the dielectric loss is mainly dominant, and the loss capacity is more stable.

[0046] Comparative Example

[0047] The performance of the MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing material prepared in Example 1 of the present invention is compared with that of various absorbing materials reported in relevant literature, including loading amount, minimum reflection loss, maximum effective absorption bandwidth and thickness. The specific comparison results are shown in Table 1 below.

[0048] Table 1

[0049]

[0050]

[0051] Among them, MXene-SiCnw is from the literature: Wang, Y.; Dou, Q.; Jiang, W.; Su, K.; You, J.; Yin, S.; Wang, T.; Yang, J.; Li, Q. Ti3C2TX MXene Beaded SiC Nanowires for Efficient Microwave Absorption. ACS Appl. Nano Mater. 2022, 5, 9209-9222; MXene / ZnIn2S4 is from the literature: Li, X.; Wang, G.; Li, Q.; Wang, Y.; Lu, X. Dual optimized Ti3C2Tx MXene@ZnIn2S4 Heterostructure Based on Interface and Vacancy Engineering for Improving Electromagnetic Absorption. Chem. Eng. J. 2023, 453, No. 139488; NiCo2O4 NSs-MXene is from the literature: Zeng, X.; Zhao, C.; Yin, Y.; Nie, T.; Xie, N.; Yu, R.; Stucky, G. D. Construction of NiCo2O4 Nanosheets-Covered Ti3C2Tx MXene Heterostructure for Remarkable Electromagnetic Microwave Absorption. Carbon 2022, 193, 26-34; MXene@GO is from the literature: Li, Y.; Meng, F.; Mei, Y.; Wang, H.; Guo, Y.; Wang, Y.; Peng, F.; Huang, F.; Zhou, Z. Electrospun Generation of Ti3C2Tx MXene@graphene Oxide Hybrid Aerogel Microspheres for Tunable High Performance Microwave Absorption. Chem. Eng. J. 2020, 391, No.123512; MXene / CoNi / N-CNT from the literature: Designed 3D heterostructure with 0D / 1D / 2D hierarchy for low-frequency microwave absorption in the S-band; CNT-MXene-F-rGO from the literature: Fabrication of multi-dimensional heterostructure towards highly efficient microwave absorbing performance and flame retardancy.; CoFeAl-LDH / G from the literature: hybrids Laminated graphene oxide-supported high-efficiency microwave absorber fabricated by an in situ growth approach; NiCo-LDH / MXene from the literature: Synthesis of NiCo-LDH / MXene hybrids with abundant heterojunction surfaces as a lightweight electromagnetic wave absorber; CoNiM@C (M = Cu, Fe, Mn) from the literature: MOFs-Derived Strategy and Ternary Alloys Regulation in Flower-Like Magnetic-Carbon Microspheres with Broadband Electromagnetic Wave Absorption.

[0052] As can be seen from Table 1, compared with other types of absorbing materials, the synthesized MXene-NiCoCu-Fe-CNT nanocomposite hydrotalcite absorbing materials also have some advantages in terms of load, minimum reflection loss, maximum effective absorption bandwidth and thickness. At the same time, in terms of preparation cost, traditional hydrotalcite absorbing materials often need to add a large amount of MXene, graphene, silicon carbide nanowires and other materials with good conductive properties to increase the dielectric loss capacity of the absorbing materials. The complex preparation methods and high prices of these materials hinder their further large-scale application in the field of absorbing. The present invention uses a carbon nanotube composite conductive agent with a lower cost, whose price-to-weight ratio is only one percent of that of ordinary carbon nanotubes, to replace MXene to adjust the dielectric loss of the material, and reduce the content of MXene from 75%wt in the NiCo-LDH / MXene literature report to 0.5%wt, which greatly reduces the amount of MXene while maintaining the good dielectric loss capacity of the material.

[0053] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a multidimensional nanocomposite absorbing material, characterized in that: The preparation method comprises: mixing nickel salt hydrate, cobalt salt hydrate and copper salt hydrate according to a designed ratio and dissolving them in water to form liquid A; preparing alkaline liquid B; then adding MXene dispersion into a container, adding liquid A and liquid B dropwise, so that the mixed liquid maintains an alkaline environment; then adding carbon nanotube composite conductive agent and Fe3O4 nanoparticles, reacting at room temperature and then heating, and finally centrifuging and washing the product.

2. The method for preparing the multidimensional nanocomposite absorbing material according to claim 1, characterized in that: The molar ratio of the nickel salt hydrate, the cobalt salt hydrate and the copper salt hydrate is (4.5-5.5):(1.5-2.5):

1.

3. The method for preparing the multidimensional nanocomposite absorbing material according to claim 1 or 2, characterized in that: The nickel salt hydrate is selected from NiCl2·6H2O, Ni(NO3)2·6H2O or NiSO4·6H2O, the cobalt salt hydrate is selected from CoCl2·6H2O, Co(NO3)2·6H2O or CoSO4·6H2O, and the copper salt hydrate is selected from CuCl2·2H2O, Cu(NO3)2·3H2O or CuSO4·5H2O.

4. The method for preparing the multidimensional nanocomposite absorbing material according to claim 1, characterized in that: The alkaline solution B is prepared by mixing a NaOH solution and a Na2CO3 solution.

5. The method for preparing the multidimensional nanocomposite absorbing material according to claim 1 or 4, characterized in that: The pH value of the mixed solution is maintained at 9.5-10.

5.

6. The method for preparing the multi-dimensional nanocomposite absorbing material according to claim 1, characterized in that: The mass ratio of the MXene, carbon nanotube composite conductive agent and Fe3O4 nanoparticles is (3.75-10):(100-200):(231-462).

7. The method for preparing a multi-dimensional nanocomposite absorbing material according to claim 1, characterized in that: The room temperature reaction time is 0.5-1.5 hours, and the heating treatment is carried out in a water bath at 70° C. for 3.5-4.5 hours.

8. A multi-dimensional nanocomposite absorbing material, characterized in that: The multidimensional nanocomposite absorbing material is prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the multidimensional nanocomposite absorbing material as claimed in claim 8, characterized in that: The multi-dimensional nano composite wave absorbing material is used for stealth coatings, satellite radars or electromagnetic shielding of electronic equipment.

10. The use according to claim 9, characterized in that: The thickness of the multi-dimensional nano-composite wave absorbing material is 2-6 mm.

Citation Information

Patent Citations

  • Wave-absorbing material with zero-dimensional / one-dimensional / two-dimensional composite nanostructure as well as preparation method and application of wave-absorbing material

    CN114501966A

  • Ni-Co LDH-coated MXene high-performance electrode and preparation method thereof

    CN114512347A

  • Composite film with electromagnetic shielding and heat-conducting properties and preparation method thereof

    CN115348815A

  • Magnetic metal CoNiZn-coated Ti3CNTx-coated C composite material as well as preparation method and application thereof

    CN117025171A

  • MXene Co-C / carbon nanotube composite wave-absorbing material and preparation method thereof

    CN117794205A